A system for designing and 3D printing of porous structures. Issue 1 (2020) - Ullah, A.M.M. Sharif; Kiuno, Hiroki; Kubo, Akihiko; D'Addona, Doriana Marilena
Abstract: Porous structures exhibit superior properties compared to their non-porous counterparts, though they are challenging to design and fabricate. This paper presents a self-contained and user-friendly system that designs a porous structure by filling the spaces between a randomly generated point cloud and a closed boundary. It produces the STL dataset of the designed structure. The system generated STL datasets were used to fabricate some porous structures using a 3D printer. The fabricated structures exhibited randomly sized and distributed pores through which gasses and liquids could pass. These characteristics of the fabricated structures make them suitable for engineering and biomedical applications.